Intertemporal substitution in labor force participation: Evidence from policy discontinuities - Dayanand Manoli; Andrea Maria Weber (Institute for the Study of Labor (IZA), 2010)
This paper presents new empirical evidence on intertemporal labor supply elasticities. Weuse administrative data on the census of private sector employees in Austria and variation from mandated discontinuous changes in retirement benefits from the Austrian pension system. We first present graphical evidence documenting delays in retirement in response to the policy discontinuities. Next, based on the empirical evidence, we develop a model of career length decisions. Using an estimator that exploits the graphical evidence, we estimate an intertemporal labor supply elasticity of 0.30; this relatively low estimate reflects that the disutility of labor supply rises relatively quickly with additional years of work.
Keywords: J22; J26; E24; 330; life-cycle labor supply; retirement decisions; intertemporal labor supply elasticity; policy discontinuitie